AJIC Issue 25, 2020 - Full Issue - (:unkn) unknown (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2020)
Articles on digital terrorism, SMS fraud, machine learning, mHealth, natural language processing, and international telecommunications law and policy.